EFFECT OF ORGANIZATIONAL CULTURE, WORK COMMITMENT AND MANAGEMENT KNOWLEDGE ON EMPLOYEE ACHIEVEMENT MOTIVATION IN THE ENVIRONMENT MINISTRY OF RELIGION OF JAMBI PROVINCE - Mukhtar; Risnita; Nurazmi (International Journal of Research -GRANTHAALAYAH, 2019)
This study aims to examine the effect of exogenous variables on endogenous variables either partially or simultaneously. The research objectives were arranged as many as 10 points. The research location in the Office of the Ministry of Religion of Jambi Province which consists of the Ministry of Religion office in Jambi City, the Office of the Ministry of Religion of TanjungJabungTimur, the Office of the Ministry of Religion of the Regency of Batanghari. This study produces ten conclusions, namely, including: 1). There is a direct influence of organizational culture (X1) on employee achievement motivation (X4). Based on the results of the calculation of the analysis obtained tcount (18,31)> t table (1.969), so that H0 is rejected and H1 is accepted. It means that organizational culture has a significant influence on employee achievement motivation. 2). There is a direct effect of work commitment (X2) on employee achievement motivation (X4). Based on the results of the calculation of the analysis obtained the value of tcount (7.61)> t table (1.969), so that H0 is rejected and H1 is accepted. It means that the work commitment that develops in the institution has a significant influence on employee achievement motivation. 3). There is a direct influence of organizational culture (X1) and work commitment (X2) on employee achievement motivation (X4). Based on the results of the calculation of the analysis obtained the value of Fcount (16.36) >Ftable (3.45), so that H0 is rejected and H1 is accepted. Meaning that the organizational culture and high management knowledge in the institution have a significant influence on employee achievement motivation. The conclusion of the study is, from the results of testing the hypothesis, it can be concluded that the 10 hypotheses are accepted, namely there are effects of exogenous variables on endogenous variables both partially and simultaneously, both directly and indirectly. The research implication is that an employee’s achievement motivation is strongly influenced by organizational culture, work commitment, and management knowledge, the better the organizational culture, the higher the work commitment and management knowledge, the higher the spirit of achievement in carrying out a job.